THE USE OF NOUN PHRASE IN SCIENTIFIC SENTENCE - WENI AYU SUNITA ZANDROTO; NURAINI ADE PUTRI LUBIS; WANAPRI PANGARIBUAN; YUNIARTO MUDJISUSATYO (LINGUISTICA, 2024)
The purpose of this research is to identify the types and patterns of the noun phrase. The aim of this research is to identify the types and patterns of word combinations that form noun phrases in journal articles published by BJA educational article with the title "Being a good educational supervisor". The research method used is a literature study with a qualitative descriptive approach data obtained from articles published by BJA education articles. The results of the analysis show varying patterns of use of noun phrases. Combinations of words that form noun phrases in journal articles published by BJA educational article with the title "Being a good educational supervisor". This research attempts to discuss the use of noun phrases among researchers in their research reports. It examines not only the correct usage but also the inappropriate use of noun phrases. The research method used is a literature study with a qualitative descriptive approach data obtained from articles published by BJA education articles. The results of the analysis show varied patterns of noun phrase use.